Evaluation of bond strength of orthodontic brackets using light- and chemical-cure adhesive systems over time: An in-vitro study - Maryam Omidkhoda; Neda Eslami; Maryam Mazloum; Mostafa Entezari (Wolters Kluwer Medknow Publications, 2023)
AIMS: This study aimed to evaluate the bond strength of light- and chemical-cure adhesive systems over six months. MATERIALS AND METHODS: A total of 144 sound human maxillary first and second premolars were randomly divided into six groups according to the adhesive type (i.e., Transbond XT and Unite) and evaluation time. The groups were T0 (24-h group without thermocycling), T1 (24-h group with thermocycling), T2 (1-month group), T3 (2-month group), T4 (4-month group), and T5 (6-month group). The bond strength was then measured and the data were analyzed by SPSS software (version 23) through the independent t-test and one-way ANOVA. A P value less than 0.05 was considered statistically significant. RESULTS: The results of this study showed that shear bond strength of chemical-cure orthodontic adhesive (Unite, 15.37 MPa) at all-time points was significantly 1.37 times higher than that of the Transbond XT light-cure adhesive (11.15 MPa). Moreover, shear bond strength of self-cure adhesive (Unite) 1 month after debonding showed a significant difference with the 24-h group without thermocycling (P = 0.002), 24-h group with thermocycling (P = 0.008), and 6-month group (P = 0.016). The highest shear bond strength in both adhesives was observed at one month. Furthermore, the shear bond strength of Transbond XT light-cure adhesive one month after debonding showed a significant difference with the 24-h group without thermocycling (P = 0.000) and 24-h group with thermocycling (P = 0.000), as well as with the 2-month (P = 0.008), 4-month (P = 0.000), and 6-month groups (P = 0.016). CONCLUSION: Unite self-cure adhesive compared to Transbond XT light-cure adhesive has higher bond strength and is recommended for rebonding brackets in patients with multiple rebonds.